Current Status of Lymphadenectomy during Radical Resection of Intrahepatic Cholangiocarcinoma: a Single-center Retrospective Study - HU Chao, CHENG Xi, JIN Wangxun, YAO Hongqing, WANG Xinbao (Zhongguo quanke yixue, 2023)
Background Lymph node metastasis is an important factor affecting the prognosis of patients with intrahepatic cholangiocarcinoma, but lymphadenectomy extent remains controversial both domestically and internationally. Objective To explore the current status of lymphadenectomy during radical resection of intrahepatic cholangiocarcinoma. Methods A retrospective analysis of the clinical data of 152 patients with intrahepatic cholangiocarcinoma who underwent radical resection at Zhejiang Cancer Hospital from 2017 to 2022 was conducted to determine the current status of lymphadenectomy during radical resection of intrahepatic cholangiocarcinoma, including the decision to perform lymphadenectomy, the extent of lymphadenectomy and the distribution of positive lymph nodes. The patients were divided into the left hemi-liver group and right hemi-liver group according to the location of the tumour in the liver. Results A total of 152 patients were selected, including 83 patients in the left hemi-liver group and 69 in the right hemi-liver group. Eighty-six of them underwently mphadenectomy, accounting for higher proportion in the left hemi-liver group〔61 cases (73.5%) 〕 than the right hemi-liver group〔25 cases (36.2%) 〕 (P<0.05) . The average number of dissected lymph nodes was (7.6±6.1) , with no significant difference between the left〔7.0 (4.0, 10.5) 〕 and right hemi-liver groups 〔5.0 (1.5, 9.5) 〕 (P>0.05) . Of the 86 patients underwent lymphadenectomy, 39 (45.3%) cases showed lymph node metastasis (positive lymph nodes) on pathological examination, accounting for higher proportion in the left hemi-liver group〔34 cases (55.7%) 〕 than the right hemi-liver group〔5 cases (20.0%) 〕 (P<0.05) . Regardless of which lobe the tumour was located, lymph node stations 8, 12, and 13 accounted for a higher proportion of metastasis in routine dissection areas, among which the proportion of lymph nodes station 12 was the highest, with 79.4% (27/34) in the left hemi-liver group and 80.0% (4/5) in the right hemi-liver group. Conclusion Regardless of the location of tumour, lymph node stations 8, 12 and 13 have a higher incidence of lymph node metastasis and should be considered for routine dissection during radical resection.